The impact of technology on banks distribution channels / Cik Khuzaimah Abdul Malek - Abdul Malek, Cik Khuzaimah (1997)
This research studies on the impact of technology on banks distribution channels. There are various types of banks' distribution channels, but this study will focus only on Automated Teller Machines ( ATM ) and home banking because they are the latest technology being implemented by the banks and well accepted by the customers. The performance will be looked from the overall information technology expenditure and the types of delivery channels in the banking industry, by looking at each sector, commercial banks, finance companies and merchant banks. It will cover the study of five consecutive years, 1991- 1995. It is concluded that these distribution channels have been proven successful and well accepted by the customers and the bankers where it gives fast and convenient services to customers with lower costs incurred by the bank. It is also hoped that the findings of this research will provide some new and practical insight into the quality of services provided by banks in Malaysia.